Computer mediated communication for construction-supported constructivism in communication and cultural learning - Wayan Sintawati (International Journal of Communication and Society, 2019)
This paper aims to explain how CMC has implications for constructivism in communication and cultural learning. he method used to write this review followed previous patterns by work. During collecting articles as main sources, we used Google scholar, Baidu scholars, Science Direct and Mendeley search platform, we also used such keywords as cross-cultural learning, technology, intercultural learning, promoting, facilitating, understanding and competence to find articles. in the end in this paper found conclusions Technology-used should fulfil the today need of learner. Combination of asynchronous and synchronous communication are mostly suggested for the next future research. We also believe by the need of global society and the rapid growth of technology, people around the world need more advanced technology such as Hologram, VR technology, artificial intelligent features, cloud and so on.